Pengaruh Model Problem-Based Learning Terintegrasi Etnosains Terhadap Kemampuan Berpikir Kritis Peserta Didik SD - Nawang Lutfia Sani; Frida Destini; Niken Yuni Astiti (Didaktika Dwija Indria, 2026)
The problem in this study is the low critical thinking skills of students in IPAS subjects in grade IV elementary school. The purpose of this study is to determine the effect of using the Problem-Based Learning model integrated with ethnoscience on critical thinking skills in IPAS subjects in grade IV elementary school. The study used a quantitative method with a quasi-experimental non-equivalent control group design.The population and sample in this study were obtained through purposive sampling with a sample size of 48 students. Data collection techniques included tests and non-tests. The data were tested for hypotheses using simple linear regression tests. The results of the study indicate that the use of the ethnoscience-integrated Problem-Based Learning model has an effect on critical thinking skills in fourth-grade  IPAS subjects in elementary schools.